Morphological Variation of the Asian Honeybee Apis cerana (F.) (Hymenoptera: Apidae) in West Java. The diversity of Asian honeybee Apis cerana (F.) (Hymenoptera: Apidae) occupying low and high altitude habitats in West Java was studied using morphological analysis, based on the length of proboscis, hindleg, front wing, tergites, and sternites. All morphological characters measured were signifcantly longer in high altitude bees compareded to those of low altitude bees (p < 0.05), except proboscis - Rika Raffiudin; Soemartono Sosmarsono; endang S. Ratna; Dedy D. Solihin (Buletin Hama dan Penyakit Tumbuhan, 1999)
Morphological Variation of the Asian Honeybee Apis cerana (F.) (Hymenoptera: Apidae) in West Java. The diversity of Asian honeybee Apis cerana (F.) (Hymenoptera: Apidae) occupying low and high altitude habitats in West Java was studied using morphological analysis, based on the length of proboscis, hindleg, front wing, tergites, and sternites. All morphological characters measured were signifcantly longer in high altitude bees compareded to those of low altitude bees (p < 0.05), except proboscis. Dendogram analysis showed that bees from those two altitudes were separated, whereas the result of principal component analysis indicated that both belong to the same group (P < 0.05).